2021
DOI: 10.1101/2021.12.01.470847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A nickase Cas9 gene-drive system promotes super-Mendelian inheritance in Drosophila

Abstract: CRISPR-based gene drive systems can be used to modify entire wild populations due to their ability to bias their own inheritance towards super-Mendelian rates (>100%). Current gene drives contain a Cas9 and a gRNA gene inserted at the location targeted by the gRNA. These gene products are able to cut the opposing wildtype allele, and lead to its replacement with a copy of the gene drive through the homology-directed DNA repair pathway. When this allelic conversion occurs in the germline it leads to the pref… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We took our analysis further by comparing the relative efficiencies of HTR processes following DSB or nicks targeting opposing DNA strands. For these experiments, we made use of three equivalent transgenic cassettes inserted at the same site to express either Cas9, D10A, or the alternate H840A nickase at identical levels to repair the CS1 − allele ( 23 ). H840A is mutated in the HNH catalytic domain and thus produces SSB on the opposite nontargeted DNA strand from that cleaved by D10A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took our analysis further by comparing the relative efficiencies of HTR processes following DSB or nicks targeting opposing DNA strands. For these experiments, we made use of three equivalent transgenic cassettes inserted at the same site to express either Cas9, D10A, or the alternate H840A nickase at identical levels to repair the CS1 − allele ( 23 ). H840A is mutated in the HNH catalytic domain and thus produces SSB on the opposite nontargeted DNA strand from that cleaved by D10A.…”
Section: Resultsmentioning
confidence: 99%
“…For comparing the activity of the different nucleases and deep sequencing analysis (Fig. 3), three lines were designed in which vasaCas9, vasaD10A, or vasaH840A sequences associated with the DsRed marker were inserted at the same location in the yellow gene ( 23 ). For pairing-independent HDR (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that any individual cut site in a classical multiplexing may be less efficient than a drive element optimised for only one cut site. Nonetheless, additional studies have indicated that multiplexing can increase the overall efficiency of a HEG albeit in some cases with diminishing returns for additional gRNAs ( Champer et al, 2018 , Champer et al, 2020 S. E. ; Yang et al, 2021 ), and ( López Del Amo et al, 2021 ) compared to ( López Del Amo et al, 2020b ).…”
Section: What Strategies Do We Have To Combat These Challenges?mentioning
confidence: 99%